The Relationship Between Feeding Patterns and The Incidence of Stunting in Toddlers (Age 1-5 Years) in Posyandu Mawar 5 Sukasari Village, Karangtengah Sub- District, Cianjur District - Syifa Fauziah; Sri Hartati; Shinta Arini Ayu; Papat Patimah (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Stunting remains a major global health issue, affecting over 160 million children under five. In Indonesia, the prevalence is still high, posing a threat to optimal child development. This study aims to determine the relationship between feeding patterns and the incidence of stunting in toddlers (aged 1-5 years) at Posyandu Mawar 5, Sukasari Village, Karangtengah District, Cianjur Regency. A cross-sectional descriptive-analytic study was conducted involving 53 toddlers and their mothers using total sampling. Data were collected through a validated questionnaire on feeding patterns and anthropometric measurements. Statistical analysis was performed using the Spearman rank test. The findings showed that 67.9% of toddlers received appropriate feeding, while 32.1% did not. Among toddlers with inappropriate feeding, all were stunted (32.1%). A significant relationship was found between feeding patterns and stunting (p < 0.001). Inappropriate feeding patterns are strongly associated with the incidence of stunting in toddlers. Educational efforts for mothers regarding proper nutrition and feeding practices are essential in preventing stunting.